Efficacy of a First-Grade Mathematics Intervention on Measurement and Data Analysis. (October 2019) - Doabler, Christian T.; Clarke, Ben; Kosty, Derek; Turtura, Jessica E.; Firestone, Allison R.; Smolkowski, Keith; Jungjohann, Kathleen; Brafford, Tasia L.; Nelson, Nancy J.; Sutherland, Marah; Fien, Hank; Maddox, Steven A.
Well-designed mathematics instruction focused on concepts and problem-solving skills associated with measurement and data analysis can build a foundational understanding for more advanced mathematics. This study investigated the efficacy of the Precision Mathematics Level 1 (PM-L1) intervention, a Tier 2 print- and technology-based mathematics intervention designed to increase first-grade students' conceptual understanding and problem-solving skills around the areas of measurement and data analysis. Employing a randomized controlled trial, 96 first-grade students at risk for mathematics difficulties were randomly assigned within classrooms to either a treatment (PM-L1) or a control (business-as-usual) condition. A statistically significant positive effect was found on one of five outcome measures, with the other four showing positive but nonsignificant results. Results also suggested preliminary evidence of differential response based on students' number sense and early literacy risk status. Implications for using mathematics interventions focused on measurement and data analysis to build comprehensive, multitiered service delivery models in mathematics are discussed.